2012
DOI: 10.1063/1.4747339
|View full text |Cite
|
Sign up to set email alerts
|

Relating normal vibrational modes to local vibrational modes with the help of an adiabatic connection scheme

Abstract: Information on the electronic structure of a molecule and its chemical bonds is encoded in the molecular normal vibrational modes. However, normal vibrational modes result from a coupling of local vibrational modes, which means that only the latter can provide detailed insight into bonding and other structural features. In this work, it is proven that the adiabatic internal coordinate vibrational modes of Konkoli and Cremer [Int. J. Quantum Chem. 67, 29 (1998)] represent a unique set of local modes that is dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
185
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(193 citation statements)
references
References 65 publications
(106 reference statements)
4
185
0
3
Order By: Relevance
“…Beside complex binding energy, geometry, and vibrational frequencies, infrared and Raman spectra including the Raman depolarization ratio [16] were calculated. The local vibrational modes were derived according to Konkoli and Cremer [18,29] where the relationship between normal and local vibrational frequencies was determined with the adiabatic connection scheme (ACS) [30,31]. For each normal mode frequency the corresponding local mode and coupling frequencies were determined and checked whether they lead to the conservation of the zeropoint energy of the molecule.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside complex binding energy, geometry, and vibrational frequencies, infrared and Raman spectra including the Raman depolarization ratio [16] were calculated. The local vibrational modes were derived according to Konkoli and Cremer [18,29] where the relationship between normal and local vibrational frequencies was determined with the adiabatic connection scheme (ACS) [30,31]. For each normal mode frequency the corresponding local mode and coupling frequencies were determined and checked whether they lead to the conservation of the zeropoint energy of the molecule.…”
Section: Methodsmentioning
confidence: 99%
“…Vibrational modes probe the electronic structure and the bonds of a molecule or a molecular complex. Therefore, the stretching force constants provide a direct measure of the strength of the bonds of a molecule and the bending force constants about bond-bond interactions based on hybridization, electrostatic, and/or polarization effects [18,29,17,32,30,35].…”
Section: Detection Of Pnicogen Bonding With Vibrational Spectroscopymentioning
confidence: 99%
“…[37] All-electron basis sets aug-ccpVTZ were used for H, Cl, [38] C, and N. By using the AIMALL program, [22] atom-in-molecule (AIM) analyses were performed to determine the electron delocalization between metals and ligands. The adiabatic force constants were determined by using the code developed by Cremer and co-workers [39] based on the force constant matrix from DFT/B3LYP calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…15,16 In addition, in comparison with independent physical properties, other groups have successfully applied compliance constants and confirmed the significance of our results. 3,17 Very recently, in an elegant series (see for example 18 ) of papers, Cremer et al have shown that the so called local mode force constants introduced in 1998 19 amount exactly to (inverse) compliance constants introduced as early as 1947. 20 It is important to note that, as a second order tensor, the compliance matrix contains non-zero coupling elements.…”
mentioning
confidence: 99%
“…If this tensor property is ignored and/or oversimplified potential functions are used, problems concerning the interpretation of compliance constants may arise. [21][22][23][24] The interpretation of exactly those coupling terms seems to have caused some troubles in the literature, 18 culminating in the conclusion that ''compliance constants are not useful diagnostics of the strength of weak interatomic interactions'' at all. 21,22 In order to verify, or falsify, this finding and to further elucidate the interpretation of compliance off-diagonal terms, the following study was split into two parts: in part one, we present detailed results on a series of rare gas-hydrogen iodide complexes comprising solely of van der Waals bonding.…”
mentioning
confidence: 99%